Analysis of the Influence of Profitability Performance, Credit Risk, Liquidity Risk and Capital Adequacy on the Value of Banking Sector Companies Listed on the Indonesian Stock Exchange for the Period 2015 – 2021 - Siti Safarina; Tris Sudarto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The value of a bank can be determined by its level of profitability and risk. Banks also need sufficient capital to continue to develop their business and increase their company value. This research aims to examine and analyze the influence of profitability performance, credit risk, liquidity risk and capital adequacy on the value of banking companies in Indonesia. The population in this research are banking companies listed on the Indonesia Stock Exchange for the period 2015 - 2021. The sampling technique used was the purposive sampling method, while the analysis method used was multiple linear regression analysis using EViews-12. The results of this research show that profitability performance (ROA) and credit risk (NPL) have no effect on company value, while liquidity risk (LDR) and capital adequacy (CAR) have a positive effect on company value.